Solid-immersion super-oscillatory lens for heat assisted magnetic recording technology and nanoscale imaging - Roy, Tapashree (2018)
We demonstrate a solid-immersion super-oscillatory planar lens for super-resolution applications with a 102 nm full-width at half maximum focal spot in a low-loss immersion medium.